DEALING WITH MESSINESS AND UNCERTAINTY IN PRACTITIONER RESEARCH: THE NATURE OF PARTICIPATORY ACTION RESEARCH - Goodnough, Karen (Canadian Journal of Education/Revue canadienne de l'éducation, 2008)
This article reports on the experiences and perceptions of K‐12 teachers as they engaged in a participatory action research (PAR) project, Science Across the Curriculum. Although the experiences and professional learning of two of the project participants are highlighted, the challenges that all participants experienced as they conceptual‐ ized and implemented action research are also reported. The author concludes that messiness and uncertainty are inherent and necessary elements of action research and that these elements need to be explicit for the benefit of those who engage in and facilitate PAR. Key words: science education, teacher development, teacher inquiry Cet article présente les expériences et les perceptions d’enseignants de la maternelle au secondaire qui ont pris part à une recherche‐action participative (RAP), Science Across the Curriculum. Ce sont surtout les expériences et l’apprentissage professionnel de deux des participants qui sont mis en lumière, mais l’article fait également état des défis auxquels ont fait face tous les participants dans la conceptualisation et la mise en œuvre de la recherche‐action. L’auteure conclut que la désorganisation et l’incertitude sont des éléments intrinsèques de la recherche‐action et que ces éléments doivent être explicites pour le plus grand bien des personnes qui participent et animent une RAP. Mots clés: recherche‐action participative, perfectionnement des enseignants, recherche sur les enseignants